Plasma concentrations and behavioral, antinociceptive, and physiologic effects of methadone after intravenous and oral transmucosal administration in cats - Ferreira, Tatiana H. [UNESP]; Rezende, Marlis L.; Mama, Khursheed R.; Hudachek, Susan E.; Aguiar, Antonio J. A. [UNESP] (Amer Veterinary Medical Assoc, 2011)
Objective-To determine plasma concentrations and behavioral, antinociceptive, and physiologic effects of methadone administered via IV and oral transmucosal (OTM) routes in cats.Animals-8 healthy adult cats.Procedures-Methadone was administered via IV (0.3 mg/kg) and OTM (0.6 mg/kg) routes to each cat in a balanced crossover design. on the days of drug administration, jugular catheters were placed in all cats under anesthesia; a cephalic catheter was also placed in cats that received methadone IV Baseline measurements were obtained >= 90 minutes after extubation, and methadone was administered via the predetermined route. Heart and respiratory rates were measured; sedation, behavior, and antinociception were evaluated, and blood samples were collected for methadone concentration analysis at predetermined intervals for 24 hours after methadone administration. Data were summarized and evaluated statistically.Results-Plasma concentrations of methadone were detected rapidly after administration via either route. Peak concentration was detected 2 hours after OTM administration and 10 minutes after IV administration. Mean +/- SD peak concentration was lower after OTM administration (81.2 +/- 14.5 ng/mL) than after IV administration (112.9 +/- 28.5 ng/mL). Sedation was greater and lasted longer after OTM administration. Antinociceptive effects were detected 10 minutes after administration in both groups; these persisted 2 hours after IV administration and 4 hours after OTM administration.Conclusions and Clinical Relevance-Despite lower mean peak plasma concentrations, duration of antinociceptive effects of methadone was longer after OTM administration than after IV administration. Methadone administered via either route may be useful for perioperative pain management in cats. (Am J Vet Res 2011;72:764-771)